Potential biocontrol for bacterial and viral disease treatment in aquaculture: A minireview - Zy, Chee Wong; Nur Amirah Mohamad Alwie; Lim, Leong Seng; Motohiko Sano; Mohammad Tamrin Mohamad Lal (The Society for Antibacterial and Antifungal Agents, Japan, 2024)
Aquaculture is part of the crucial industry that supplies food, especially for the global human population that is gradually increasing annually. Innovations of culture techniques have been improved throughout the years but aquaculture is regularly susceptible to bacterial and viral diseases. Numerous factors could contribute to occurrence of disease and usually they are from environmental or human stressors on the cultured animals. Synthetic chemicals in commercial treatments may yield fast results however, the side effects are usually unknown until it has taken effect. Therefore, biological control methods to treat diseases in aquaculture are preferred. This mini review provides an overview of different potential biocontrol practices for treatment of bacterial and viral diseases. Bacteriophage causes death of pathogenic bacteria by killing the cell and continue to multiply until all targeted pathogenic bacteria are eliminated. Probiotic, prebiotic, synbiotic, biofloc, and immunostimulants are beneficial products from the respective organisms that are effective in inhibiting pathogens. Vaccines introduce inactivated pathogen into the body to stimulate the immune system, while genetic modifications involve alteration and selection of disease resistant genetics.